2004
DOI: 10.4321/s0212-71992004000500009
|View full text |Cite
|
Sign up to set email alerts
|

Sífilis secundaria nodular en paciente VIH positivo simulando linfoma cutáneo

Abstract: INTRODUCCIÓNActualmente se observa un reducido número de casos de sífilis secundaria debido al cambio de comportamientos sexuales en relación con el SIDA y la eficacia del tratamiento con penicilina; por tanto para diagnosticar a la "gran simuladora" se debe mantener un alto grado de sospecha clínica. Nosotros describimos un patrón atípico, tipo nodular, de sífilis secundaria, y comentamos algunas peculiaridades clínicas, serológicas y terapéuticas de la sífilis en los pacientes VIH positivos.CASO APORTADO Se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…On the other hand, we found four (20%) papular cases, all accompanied with mucous patches and located on dorsal tongue, as it has been described by others [ 15 , 16 ]. The term papular refers to red, raised, firm round nodules with a grey center that may ulcerate [ 36 ]; in this respect, we found that nodular lesions were covered by a depapillated surface, as described by Dalmau et al [ 15 ] and Baniandrés-Rodríguez et al [ 16 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…On the other hand, we found four (20%) papular cases, all accompanied with mucous patches and located on dorsal tongue, as it has been described by others [ 15 , 16 ]. The term papular refers to red, raised, firm round nodules with a grey center that may ulcerate [ 36 ]; in this respect, we found that nodular lesions were covered by a depapillated surface, as described by Dalmau et al [ 15 ] and Baniandrés-Rodríguez et al [ 16 ].…”
Section: Discussionsupporting
confidence: 85%
“…In addition to mucous patches [ 14 , 17 , 48 ], shallow ulcers [ 14 , 17 ], papular [ 15 , 16 ] and macular lesions [ 19 ] have also been described in HIV-infected patients with oral syphilis. As described by Ortega et al [ 14 , 17 ] we found four cases of shallow ulcers on palate, tongue, and labial mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…[1456] An important condition that is very similar to the cutaneous lymphoma related alopecia is secondary syphilis related alopecia in human immunodeficiency virus infected patients. [7] In addition to lymphoma, alopecia is also mentioned in plasmacytoma. [8] Alopecia is an important component in paraneoplastic syndrome due to plasmacytoma.…”
mentioning
confidence: 99%